Does a visit to a blue-green space evoke positive feelings? Blue and green spaces survey in Shkodra’ Lake, Albania - Kruja, Samel; Braçe, Olta (Revista de Estudios Andaluces, 2022)
People living in urban areas must face several challenges to improve their health and well-being. The purpose of this research is to further explore how the use of urban blue and green spaces is related to the people’s mood feelings when visiting these spaces. A cross-sectional study is carried out with an adult sample population in Albania with people between 16-74 years old by an online survey. Respondents have been asked to complete the survey via the platform Google Form, from April to May 2021. The questionnaire included questions related to socio-economic characteristics, urban green and blue spaces (GBS), and self-reported feelings information. After the validation and cleaning process, a representative sample (95% level of confidence) of 530 respondents was obtained. Descriptive statistics were used to analyze indicators such as (1) sociodemographic characteristics; (2) frequency of visits in GBS in the last 4 weeks; (3) time spending during the visit; (4) activities carried out during the visit; (5) type of accompaniment; (6) the reason for not visiting GBS and the quality of GBS. The SPSS software platform was used for the statistical analyses. The frequency, percentage, mean and standard deviation calculations were used to calculate data from the sample. The Chi-square test was used to examine the relationship between the frequency of visits in blue space and the people’ mood. The study shows a significant relationship among the frequency of visits of blue and green spaces and positive mood feelings.